Linus Torvalds. (Foreign Policy)
A brief profile of Linus Torvalds, number 53 on Foreign Policy's list of the top 100 global thinkers. Torvalds, self-proclaimed “benevolent dictator” of one of the most impressive group projects ever, is important not just for what he has done, but also for what he has enabled others to do. An unassuming software engineer from Finland, Torvalds is the architect of the Linux kernel, a computer operating system developed with free and open-source software. Although Torvalds started with the first few lines of code, written at age 21 in his mother's basement in Helsinki, Linux's development has since been fueled by thousands of programmers worldwide, each offering their contributions for free.